2021
DOI: 10.1111/tbed.14251
|View full text |Cite
|
Sign up to set email alerts
|

Atypical porcine pestivirus—A widespread virus in the Swedish wild boar population

Abstract: The recently identified causative agent of congenital tremor in domestic piglets, atypical porcine pestivirus (APPV), was detected in serum from Swedish wild boar. A previous study from Sweden described APPV in domestic piglets suffering from congenital tremor, but the APPV situation in the wild boar population was unknown. In this study, 595 serum samples from wild boar originating from 13 counties in the south and central parts of Sweden, collected between 2000 and 2018, were analysed for the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
(92 reference statements)
0
6
0
1
Order By: Relevance
“…These include collisions with vehicles (Gren and Jägerbrand 2019) and trains (Trafikverket 2015) and damage to agriculture (SCB 2015, Menichetti et al 2019, Gren et al 2020) and forestry (Månsson and Jarnemo 2013, Sjölander-Lindqvist and Sandström 2019, Pfeffer et al 2021. In particular S. scrofa is also a wildlife reservoir for many pathogens (Wallander et al 2015, Stenberg et al 2022, Ernholm et al 2022, and a recent outbreak of African Swine Fever (Jordbruksverket 2023) has highlighted the importance of reliable surveillance data for the species. and red fox (V. vulpes) at both national and county levels.…”
Section: Discussionmentioning
confidence: 99%
“…These include collisions with vehicles (Gren and Jägerbrand 2019) and trains (Trafikverket 2015) and damage to agriculture (SCB 2015, Menichetti et al 2019, Gren et al 2020) and forestry (Månsson and Jarnemo 2013, Sjölander-Lindqvist and Sandström 2019, Pfeffer et al 2021. In particular S. scrofa is also a wildlife reservoir for many pathogens (Wallander et al 2015, Stenberg et al 2022, Ernholm et al 2022, and a recent outbreak of African Swine Fever (Jordbruksverket 2023) has highlighted the importance of reliable surveillance data for the species. and red fox (V. vulpes) at both national and county levels.…”
Section: Discussionmentioning
confidence: 99%
“…A serological survey of APPV among apparently healthy domestic pigs in different parts of Europe and Asia conducted by a German research group, revealed that 60% (880/1460) of the pigs displayed intermediate to high antibody levels against APPV [ 8 ]. In addition, a high APPV seroprevalence has been demonstrated in wild boars in Germany (52%, 237/456) [ 20 ] and Sweden (72%, 433/595) [ 21 ]. By far, few serological investigations on APPV have been reported among domestic pigs and wild boars in China.…”
Section: Introductionmentioning
confidence: 99%
“…ASF has never been detected in the country, but the spread within Europe and the role of European wild boar ( Sus scrofa ) is a continuous worry for Swedish pig producers. Despite biosecurity programs in pig holdings (including all-in-all-out indoor production, with hygiene locks at building entrances), the risk of disease transmission between wild boar and domestic pigs has increased due to growth of the wild boar population, and the transmission of other viruses between domestic pigs and wild boar in Sweden has been demonstrated [ 3 ].…”
Section: Introductionmentioning
confidence: 99%